Pengaruh Kualitas Pelayanan Terhadap Kinerja Pelayanan Pada Kantor Pelayanan Pajak Pratama Majalaya - Manurung Manurung; Demsi Minar (Jurnal Ekonomi Manajemen Perbankan, 2019)
The purpose of this study is : 1. To find out the State of Service Quality at KPP Pratama Majalaya, 2. To find out the Service Performance at KPP Pratama Majalaya. And 3. to find out the Effect of Service Quality on Service Performance at KPP Pratama Majalaya.The method used in this study is descriptive analysis and verification analysis. Definition of analytical descriptive research according to Sugiyono (2005: 1) is : Research conducted to determine the value of independent variables, either one variable or more (independent) without making comparisons or connecting between variables one with other variables. The t test results are as follows  < , then  rejected and  be accepted, while simultaneously obtained >  , then  accepted and  rejected, meaning service quality has an effect on service performance.